Development of healthcare applications on mobile devices - Li, Eileen Yipei (2014)
Health care industry relies heavily on manual recording and management of medical data. As the amount of data increases, medical professionals will have a hard time managing them. Human errors are likely to set in once the amount of data reaches the maximum capacity that a hospital can handle. Therefore, electronic systems are proposed to meet the needs of this industry. However, existing mobile health applications and Electronic Medical Record systems requires users to manually input medical data collected from different medical devices. This